Pengembangan E-Modul Asam Basa Berbasis Literasi Sains - Nadya Ulfa; Ani Sutiani (Universitas Negeri Padang, 2021)
Teaching material is one of the aspects to improve scientific literacy skills had by students, but based on the analysis of school textbooks, especially on acid-base materials, 2 chemistry textbook do not yet have the maximum application of scientific literacy. The aim of this research is to develop acid base e-module based on scientific literacy. The method implemented is Research and Development (R and D) method by Borg and Gall which is limited to 7 out of 10 stages. The instrument used in this study was questionnaire of validity and practicality. Validation was carried out by 5 validators while the practicality test was distributed to 2 chemistry teachers and 20 students of Class XI Science of SMA Negeri 10 Medan. Based on the validation results obtained from the validators, the average result is 4,70 which a very feasible criteria. The average value of teachers and students practicality responses was 4,60 and 4,42 with a very feasible criteria so it was concluded the acid-base e-module based on scientific literacy is valid, practical and also feasible to be used in learning activities for high school students. The follow-up of this research is to conduct a trial of the effectiveness of using e-modules in improving students’ scientific literacy skills.